X = <span>width
2x-3 = </span><span>length
</span>
![x(2x-3) = 65\\ 2x^2 - 3x - 65 = 0 \\ D=b^2-4ac=(-3)^2-4*2*(-65)=529\\ x_{1,2}= \frac{-bб \sqrt{D} }{2a}= \frac{3б 23}{4} \\ x_1=-5 \ \ \O \\ x_2=6.5 \ \](https://tex.z-dn.net/?f=x%282x-3%29%20%3D%2065%5C%5C%0A2x%5E2%20-%203x%20-%2065%20%3D%200%20%5C%5C%20D%3Db%5E2-4ac%3D%28-3%29%5E2-4%2A2%2A%28-65%29%3D529%5C%5C%0Ax_%7B1%2C2%7D%3D%20%5Cfrac%7B-b%D0%B1%20%5Csqrt%7BD%7D%20%7D%7B2a%7D%3D%20%5Cfrac%7B3%D0%B1%2023%7D%7B4%7D%20%5C%5C%20x_1%3D-5%20%20%5C%20%5C%20%5CO%20%5C%5C%20x_2%3D6.5%20%5C%20%5C%20)
width = 6.5 m
length = 2x-3 = 2*6.5 - 3 = 10 m
<span>Inertia is defined as "the tendency for a body to resist acceleration; the tendency of a body at rest to remain at rest or of a body in motion to stay in motion in a straight line unless disturbed by an external force" Therefore, both will have the same inertia since they have the same mass.</span>
Answer: graph №2.
Step-by-step explanation:
![The\ graph\ \frac{(y-3)^2}{25}+\frac{(x+1)^2}{4} > 1\ is\ shown\ in\ fig. 1\ (see \ below).\\The\ graph\ y\leq \sqrt{x+5}+2 \ is\ shown\ in\ fig. 2\ (see\ below).\\](https://tex.z-dn.net/?f=The%5C%20%20graph%5C%20%20%5Cfrac%7B%28y-3%29%5E2%7D%7B25%7D%2B%5Cfrac%7B%28x%2B1%29%5E2%7D%7B4%7D%20%3E%201%5C%20%20%20is%5C%20%20shown%5C%20%20in%5C%20%20fig.%201%5C%20%20%28see%20%5C%20below%29.%5C%5CThe%5C%20%20graph%5C%20%20y%5Cleq%20%5Csqrt%7Bx%2B5%7D%2B2%20%5C%20%20%20is%5C%20%20shown%5C%20%20in%5C%20%20fig.%202%5C%20%28see%5C%20%20below%29.%5C%5C)